PENGARUH BETA-GLUKAN DARI EKSTRAK RAGI ROTI (SACCHAROMYCES CEREVISIAE) TERHADAP PENYEMBUHAN LUKA SAYAT PADA MENCIT WIBSTAR JANTAN - MASHITHAH .; NITA ANDRINI (LP2MTBM MAKARIOZ, 2021)
The prevalence of patients with wounds is 350 per 1000 population in the world. Meanwhile, the prevalence in Indonesia is8.2%, with the highest number in South Sulawesi province, which is 12.8%. The highest causes of injuries in Indonesia areinjuries by 70.9%, injuries to falls by 40.9%, followed by motorcycle accidents by 40.6%. In general, the therapy used forwounds is povidone iodine. However, povidone iodine has irritating properties on the skin and causes toxic effects. Judgingfrom the side effects of povidone iodine, other alternatives are needed to treat wounds. According to research, the content ofactive substances such as beta-glucan has a role as anti-inflammatory and anti-bacterial. The research method used is TrueExperiment with post test only controlled group design. This study used male Wibstar mice which were given a 1cm longincision with a depth of 0.2 cm on the back. Then divided into 2 groups, namely negative control and positive control. Thepositive control was given beta-gluca from baker's yeast (saccharomyces cerevisiae) for 7 days at the same time. In the study,there were significant differences between the negative control group and the positive control group. In the T test analysisdata on day 2 the results were p <0.05. meaning that the group that was given beta-glucan from the extract of baker's yeast(saccharomyces cerevisiae) experienced a faster wound healing process. There was a significant difference between woundhealing time between the untreated group and the treated group.